Characteristics and Health Risks of PM2.5-bound Metals in a Central City of Northern China: A One-year Observation Study - Jinhe Wang; Shuang Zhang; Xiaoguo Qiu; Kai Li; Jiarong Li; Yangang Ren; Chao Zhu; Xi Zhang (Aerosol and Air Quality Research)
Abstract Metals are important components of PM2.5, with significant implications for the ecological environment and human health. This study comprehensively investigated the characteristics of 19 metals in PM2.5 samples collected in Jinan from 16 December 2020 to 15 December 2021. The total concentration of the studied metals accounted for 5.3% of PM2.5 (41.7 μg m−3) in Jinan. The seasonal variation of PM2.5-bound metals followed the order of spring (3.5 μg m−3) > winter (2.2 μg m−3) > summer (1.4 μg m−3) > autumn (1.1 μg m−3). Four sources could be extracted using the positive matrix factorization (PMF) model, namely resuspended dust (51.9%), oil combustion (19.9%), factories (16.5%), and traffic emissions (11.7%). According to the results of the enrichment factor (EF) and geo-accumulation (Igeo), Se, Sb, Tl, Ag, Cd, Zn, V, Pb, and Mo were mainly from anthropogenic sources, which was consistent with the PMF results. Applying the conditional bivariate probability function (CBPF), traffic emissions were found to be the main local contributor, with large contributions when the wind speed was lower than 2 m s−1. The environmental influence of PM2.5-bound metals was evaluated in terms of the ecological risk index, which was found to be higher than 600, indicating high ecological risk in Jinan. Regarding the human health risk, children were possibly more exposed to non-carcinogenic risks than adults, with hazard index (HI) values of 47.9 and 6.7, respectively. Moreover, the residents of Jinan were also exposed to moderate carcinogenic risk (children: 4.8 × 10−5, adults: 4.9 × 10−5), with Cr(VI), Pb, and Co as the dominant high-risk metals. Therefore, PM2.5-bound metal pollution in Jinan cannot be overlooked, and appropriate measures should be implemented.